2020
DOI: 10.1007/s13593-020-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

Mixed outcomes from conservation practices on soils and Striga-affected yields of a low-input, rice–maize system in Madagascar

Abstract: On upland soils in tropical Africa, common production constraints of rice and maize on smallholder farms are poor soil fertilityresulting from soil erosion and nutrient depletion-and infestation by witchweeds (Striga spp.). In Madagascar where these crops are often grown in rotation, combining legume cover crops with no-till and crop residue mulching-labelled conservation agriculture (CA)-may address these problems. Previously, it was shown that CA practices contribute to steep reductions in Striga asiatica in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Practising no-tillage however generally leads to higher weed biomass (Olofintoye, 1989;Saito et al, 2010a). In a rice-maize rotation a Conservation Agriculture (CA) approach with Stylosanthes guianensis as cover crop and source for mulch, controls erosion (Rodenburg et al, 2020) while the loss of weed control from refrained tillage can be compensated by its weed suppression (Randrianjafizanaka et al, 2018). Crop residue mulching may contribute to weed suppression, but earlier work showed that removal (Becker and Johnson, 1999b) or burning of residues (Akanvou et al, 2000) resulted in lower weed biomass levels in the following crop.…”
Section: Preventive Management Focussed On Weedsmentioning
confidence: 99%
“…Practising no-tillage however generally leads to higher weed biomass (Olofintoye, 1989;Saito et al, 2010a). In a rice-maize rotation a Conservation Agriculture (CA) approach with Stylosanthes guianensis as cover crop and source for mulch, controls erosion (Rodenburg et al, 2020) while the loss of weed control from refrained tillage can be compensated by its weed suppression (Randrianjafizanaka et al, 2018). Crop residue mulching may contribute to weed suppression, but earlier work showed that removal (Becker and Johnson, 1999b) or burning of residues (Akanvou et al, 2000) resulted in lower weed biomass levels in the following crop.…”
Section: Preventive Management Focussed On Weedsmentioning
confidence: 99%
“…However, there are also studies that show limited yield effects (e.g. Kitonyo et al, 2018;Rodenburg et al, 2020) or yield declines (Corbeels et al, 2014;Mupangwa et al, 2016;Rosenstock et al, 2014) following CA, or studies that only show yield increases from an integrated approach when it was combined with additional weed control and fertilizers application (e.g. Ngwira et al, 2014).…”
Section: Agronomic Impactmentioning
confidence: 99%
“…Stylosanthes spp. could be an alternative cover crop that produces high amounts of biomass (Rodenburg et al, 2020). Other solutions to reduce this trade-off are identifying alternative feed stocks (Jaleta et al, 2013;Valbuena et al, 2012), producing more maize biomass as feed, and introducing smallscale mechanization to further reduce the dependency on animals for traction (Baudron et al, 2014).…”
Section: Crop Residue Usementioning
confidence: 99%
See 1 more Smart Citation
“…Cependant, on constate une saturation progressive des bas-fonds (Breumier et al, 2018) et pour soutenir la demande croissante en riz, la recherche et ses partenaires de développement sont engagés depuis plus de trente années dans l'extension de sa culture sur le domaine strictement pluvial (Raboin et al, 2013 ;Ozaki & Sakurai, 2020). Avec comme but de développer des variétés adaptées aux contraintes spécifiques de ce domaine pluvial, le FOFIFA (acronyme malgache traduit par Centre National de Recherche Appliquée au Développement Rural) et le CIRAD (Centre de Coopération Internationale en Recherche Agronomique pour le Développement) ont lancé un programme de sélection variétale de riz pluvial spécifique pour la zone écologique d'altitude comprise entre 800 et 1 300 m. Les deux principales contraintes de cette zone sont la fertilité du sol, qui est bien moindre dans les plateaux que dans les bas-fonds (Ozaki & Sakurai, 2020) et la présence d'une plante parasite des céréales, Striga asiatica (L.) Kuntze, qui fait l'objet d'une attention particulière dans le cadre des recherches menées sur la résistance variétale du riz (Randrianjafizanaka et al, 2018 ;Rodenburg et al, 2020 ;Scott et al, 2020). Les principaux objectifs de ce programme, outre le contrôle de S. asiatica, est de veiller à une bonne efficience de l'utilisation de l'azote (Rakotoson et al, 2017), à la résistance aux maladies comme la pyriculariose (Dusserre et al, 2017) et à la qualité des grains (Raboin et al, 2014).…”
Section: Introductionunclassified